The philosophical library existentialism collection. - Sartre, Jean-Paul, 1905-1980; Heidegger, Martin, 1889-1976; Buber, Martin, 1878-1965 (Philosophical Library : Open Road, 2018)
Explore the work of three great existential philosophers together in this collection. Hasidism: Zionist philosopher Martin Buber shares the results of forty years of study and introduces the philosophies of Hasidism to a Western audience. In this modern masterpiece, Buber interprets the ideas and motives that underlie the great Jewish religious movement of Hasidism and its creator, Baal Shem. Essays in Metaphysics: German philosopher Martin Heidegger presents two lectures in which he explores the nature of identity in the history of metaphysics. He offers illuminating insights on vital issues like technology, religion, language, history, and more. The Emotions: French philosopher Jean-Paul Sartre attempts to understand the role emotions play in the human psyche. Sartre analyzes fear, lust, anguish, and melancholy while asserting that human beings begin to develop emotional capabilities from a very early age, which helps them identify and understand the emotions' names and qualities later in life.